Answer:
C. [tex] \sqrt{x + 2} - \sqrt{x}[/tex]
Step-by-step explanation:
[tex] \frac{2}{ \sqrt{x} + \sqrt{x + 2} } \\ \\ = \frac{2}{ (\sqrt{x} + \sqrt{x + 2}) } \times \frac{(\sqrt{x} - \sqrt{x + 2})}{(\sqrt{x} - \sqrt{x + 2})} \\ \\ = \frac{2( \sqrt{x} - \sqrt{x + 2}) }{ ({ \sqrt{x} )}^{2} - {( \sqrt{x + 2} )}^{2} } \\ \\ = \frac{2( \sqrt{x} - \sqrt{x + 2}) }{ x - {( x + 2)} } \\ \\ = \frac{2( \sqrt{x} - \sqrt{x + 2}) }{ x - x - 2 } \\ \\ = \frac{2( \sqrt{x} - \sqrt{x + 2}) }{ - 2 } \\ \\ = - ( \sqrt{x} - \sqrt{x + 2}) \\ \\ \frac{2}{ \sqrt{x} + \sqrt{x + 2} } = \purple{ \bold{\sqrt{x + 2} - \sqrt{x} }}[/tex]